The Solar Neighborhood. XLIX. New Discoveries and Orbits of M-dwarf Multiples with Speckle Interferometry at SOAR - Vrijmoet, E.H.; Tokovinin, A.; Henry, T.J.; Winters, J.G.; Horch, E.; Jao, W.-C. (Astronomical Journal, 2022)
We present the first results of a multiyear program to map the orbits of M-dwarf multiples within 25 pc. The observations were conducted primarily during 2019-2020 using speckle interferometry at the Southern Astrophysical Research Telescope in Chile, using the High-Resolution Camera mounted on the adaptive optics module (HRCam+SAM). The sample of nearby M dwarfs is drawn from three sources: multiples from the RECONS long-term astrometric monitoring program at the SMARTS 0.9 m; known multiples, for which these new observations will enable or improve orbit fits; and candidate multiples flagged by their astrometric fits in Gaia Data Release 2 (DR2). We surveyed 333 of our 338 M dwarfs via 830 speckle observations, detecting companions for 63% of the stars. Most notably, this includes new companions for 76% of the subset selected from Gaia DR2. In all, we report the first direct detections of 97 new stellar companions to the observed M dwarfs. Here we present the properties of those detections, the limits of each nondetection, and five orbits with periods 0.67-29 yr already observed as part of this program. Companions detected have projected separations of 0.″024-2.″0 (0.25-66 au) from their primaries and have ΔI ≲ 5.0 mag. This multiyear campaign will ultimately map complete orbits for nearby M dwarfs with periods up to 3 yr, and provide key epochs to stretch orbital determinations for binaries to 30 yr. © 2022. The Author(s). Published by the American Astronomical Society.
Keywords: dept.phy; peer-reviewed

Orbital Architectures of M Dwarf Systems: Building the Mass-Luminosity Relation in the I-Band - Vrijmoet, E. H.; Henry, T.; Tokovinin, A.; Horch, E.; Jao, W.; Winters, J.; Recons Team (Bulletin of the American Astronomical Society, 2021)
M dwarfs dominate the solar neighborhood population, accounting for three of every four stars. Their broad mass range — from 62% down to 8% that of the Sun — creates a rich dynamical laboratory that can be used to challenge stellar and binary formation models. Our Orbital Architectures project is constructing a large sample of orbits for nearby M dwarf systems to establish their distributions in period, mass ratio, semimajor axis, and eccentricity, with the goal of building crucial empirical evidence that will constrain models of multi-star formation and evolution. These orbits have been observed during the 20+ year RECONS astrometry program at the CTIO/SMARTS 0.9m, enhanced by a new speckle interferometry campaign at SOAR with HRCam+SAM to map the shorter-period orbits. Together, these observing efforts will map ~120 orbits of nearby M dwarfs with orbital periods spanning 0 to 30 years, providing the richest set of data ever collected for these ubiquitous stars. The speckle observations at SOAR resolve systems and provide magnitude differences between components, many of which already have orbits mapped by the RECONS astrometry program. The synergy of 0.9m and SOAR observations allows us to determine individual component masses, and to compare those masses to their fluxes in the Kron-Cousins I band. Here we present a new mass-luminosity relation for M dwarfs in the I band, populated with 40 masses focused on the low-mass end of the M dwarf sequence. This work has been supported by NSF grants AST-0507711, AST-0908402, AST-1109445, AST-141206, and AST-1715551.
Keywords: dept.phy; ⛔ No DOI found

Three Red Suns in the Sky: A Transiting, Terrestrial Planet in a Triple M-dwarf System at 6.9 pc - Winters, J.G.; Medina, A.A.; Irwin, J.M.; Charbonneau, D.; Astudillo-Defru, N.; Horch, E.P.; Eastman, J.D.; Vrijmoet, E.H.; Henry, T.J.; Diamond-Lowe, H.; Winston, E.; Barclay, T.; et al. (Astronomical Journal, 2019)
We present the discovery from Transiting Exoplanet Survey Satellite (TESS) data of LTT 1445Ab. At a distance of 6.9 pc, it is the second nearest transiting exoplanet system found to date, and the closest one known for which the primary is an M dwarf. The host stellar system consists of three mid-to-late M dwarfs in a hierarchical configuration, which are blended in one TESS pixel. We use MEarth data and results from the Science Processing Operations Center data validation report to determine that the planet transits the primary star in the system. The planet has a radius of, an orbital period of days, and an equilibrium temperature of K. With radial velocities from the High Accuracy Radial Velocity Planet Searcher, we place a 3σ upper mass limit of 8.4 on the planet. LTT 1445Ab provides one of the best opportunities to date for the spectroscopic study of the atmosphere of a terrestrial world. We also present a detailed characterization of the host stellar system. We use high-resolution spectroscopy and imaging to rule out the presence of any other close stellar or brown dwarf companions. Nineteen years of photometric monitoring of A and BC indicate a moderate amount of variability, in agreement with that observed in the TESS light-curve data. We derive a preliminary astrometric orbit for the BC pair that reveals an edge-on and eccentric configuration. The presence of a transiting planet in this system hints that the entire system may be co-planar, implying that the system may have formed from the early fragmentation of an individual protostellar core. © 2019. The American Astronomical Society. All rights reserved..
Keywords: binaries: close; dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (LTT 1445); stars: low-mass